Impact of foreign direct investments on Croatian financial growth - Zoran Ivanovic; Sinisa Bogdan; Suzana Baresa (UTMS Journal of Economics, 2014)
Foreign direct investments are for the transition and less developed countries very important source of capital. Such investments have very positive impact on country's economy in terms of employment growth, industrial production growth, gross domestic product growth, favorable effects on the balance of payments and many other positive impacts for country economy, so it's not strange that countries in the absence of its domestic investors, are trying to attract foreign investors. Foreign investors analyze in detail possibilities and risks of each country, and if the risks exceed the opportunities there will be no inflow of foreign capital. Therefore every country which is trying to attract foreign direct investments must take care about the policy and its economy and try to be most attractive as it can be.
Keywords: F21; 330; foreign direct investment; brownfield investments; greenfield investments; economic growth